2021
DOI: 10.1017/ash.2021.165
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and outcomes of a severe acute respiratory coronavirus virus 2 (SARS-CoV-2) monoclonal antibody treatment program at an academic medical center serving a high-risk patient population

Abstract: Implementation and outcomes of a severe acute respiratory coronavirus virus 2 (SARS-CoV-2) monoclonal antibody treatment program at an academic medical center serving a high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…3 A facility in our ZIP code reported that 78% of mAbs were used in BIPOC patients, comparable to our institution's 85%. 6 Thus, facilities located within BIPOC communities may be important in closing this gap, and existing relationships with these facilities, along with higher trust and accessibility, may play a role. Equitable access to medications and immunizations is important for current and future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…3 A facility in our ZIP code reported that 78% of mAbs were used in BIPOC patients, comparable to our institution's 85%. 6 Thus, facilities located within BIPOC communities may be important in closing this gap, and existing relationships with these facilities, along with higher trust and accessibility, may play a role. Equitable access to medications and immunizations is important for current and future pandemics.…”
Section: Discussionmentioning
confidence: 99%